A linear programming for Airport Privatization – “No Frills - Giri.R, Flt Lt; Babu, J.Ashok (International Journal of Psychosocial Rehabilitation, 2020)
India has the exquisite and exorbitant population. Transport system that India has various component of rail, road and off-road transport. Air Transport plays the crucial role in the country’s economic growth. As per the recent report, India stands in the third position in terms of number of flyers as per a statistic revealed by International Air Transport Association (IATA). In the competitive environment there is a need to improve the transport for a country’s economic growth. Forecasts interpret that in next twenty years air transport would have doubled the number of passengers. Advanced air transport facilities needed to accommodate the increasing volumes of air transport and sustain their operational efficiency. Long term options to maximize efficiency or productivity in both operation and resource are to be planned. The Ministry of Civil Aviation has drafted National Civil Aviation Policy 2015 to promote the growth of Indian aviation with a multiplier effect on the economy. A linear programming model has been proposed to study and exploit the intricacies of “No Frill Airports” in order to substantiate the Airport privatization policy in order to sustain and improve the airport efficiency. In order to exploit the in-depth features of the operational efficiency of airports, the DEA is adopted. The Data envelopment analysis (DEA) method is used for analyzing and evaluating the data analytics of airport privatization. DEA is a nonparametric method used in operations research and multi-output production functions and applied in many industries. DEA develops a function whose form is determined by the most efficient producers. It is a linear programming-based technique for measuring the performance efficiency of organizational units which are termed as Decision Making Units (DMUs). This technique aims to measure how efficiently a DMU uses the resources available to generate a set of outputs which are then analyzed and exploited for functional derivative which are dependable and contributing factors for airport operation. This enables the user to investigate and evaluate the intricacies of “No Frill Airports” which yields the Airport privatization for improving the airport efficiency..